Direkter und indirekter Genitiv im Älteren Ägyptisch nach dem Zeugnis der Sargtexte - Peust, Carsten (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
Based on the Coffin Text corpus, the use of the two genitive constructions (direct vs. indirect) of Earlier Egyptian is investigated. It is argued that there is no functional difference whatsoever between them, but rather that the lexeme employed in the first position is the decisive factor. Two classes of nouns are identified, one of them usually selecting the direct genitive and the other the indirect genitive. Irrespectively of these classes, the indirect genitive is always required when the nomen regens is complex. On the other hand, the complexity of the nomen rectum does not influence the choice of the genitive construction. Contrary to these rules, the indirect genitive is sometimes preferred in order to prevent ambiguity that might otherwise have occurred.